2017
DOI: 10.1111/nmo.13259
|View full text |Cite
|
Sign up to set email alerts
|

Drooling is no early sign of dysphagia in Parkinson′s disease

Abstract: Although frequent in PD, drooling and dysphagia are only weakly related and drooling cannot be viewed as an early sign of dysphagia. Our data further suggest that the underlying cause of drooling is located in the voluntary oral phase, which is negatively influenced by cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 28 publications
(67 reference statements)
3
30
0
Order By: Relevance
“…Nienstedt et al found that in 110 PD patients with a mean disease duration of 9.7 years, half had drooling, and this was associated with dysphagia. In addition, they observed that 59% of patients with severe drooling had dysphagia [35]. Drooling was, as in other studies, also associated with cognitive performance.…”
Section: Discussionsupporting
confidence: 61%
“…Nienstedt et al found that in 110 PD patients with a mean disease duration of 9.7 years, half had drooling, and this was associated with dysphagia. In addition, they observed that 59% of patients with severe drooling had dysphagia [35]. Drooling was, as in other studies, also associated with cognitive performance.…”
Section: Discussionsupporting
confidence: 61%
“…Data in this study based on the same patient collective of our previous research on the prevalence of dysphagia and its typical findings in PD …”
Section: Methodsmentioning
confidence: 99%
“…4,5 Depending on the examined patient cohort and the survey procedure, the prevalence rates for dysphagia in PD patients vary between 11% and 95%. 1,2 Several clinical factors, such as age, 6,7 gender, [8][9][10] Body Mass Index (BMI), 11 disease duration, 12 disease severity, 11,13 drooling, 14,15 deep brain stimulation (DBS), 16 depression, 17 and cognitive function 14,18 are considered risk factors for clinically relevant dysphagia. Many patients are not aware of their swallowing dysfunction and do not report dysphagia unless asked.…”
Section: Introductionmentioning
confidence: 99%
“…Increased drooling (sialorrhea) was also deemed a sign of penetration or aspiration (67) until Nienstedt et al (62,68) found that drooling cannot be considered an early sign of dysphagia. Therefore, instrumental methods [FEES and Videofluoroscopic Swallow Study (VFSS)] are the most valid and reliable methods of detecting risk of aspiration and penetration in PwPD (67,68), particularly if they present with the following four symptoms: delayed mastication, reduced lingual motility prior to transfer, aspiration, and total swallow time (69). This information is crucial when evaluating studies on swallowing therapy and the validity of outcome measures.…”
Section: Swallowing Symptomsmentioning
confidence: 99%